Smart City Priority Innovation Assessment In West Bandung Regency - Ramdhani, Rizky Fajar; Sofyan, Hady (Journal of Renewable Engineering, 2025)
This study aims to assess the implementation of smart city innovations in West Bandung Regency in 2024, focusing on evaluating user satisfaction with the priority applications that have been launched. The research method uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model to measure Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions variables, as well as their impact on customer satisfaction. Data were collected through questionnaires from public servants associated with 37 smart city innovations. The results showed that Smart Branding: Visit KBB had the highest Performance Expectancy and Facilitating Conditions scores, while BA QRIS and Smart Branding: Visit KBB applications had the highest Effort Expectancy scores. The implications of this research are to provide recommendations for improving the effectiveness and acceptance of smart city applications in West Bandung Regency, as well as providing insights for the development of future smart city programs.